On trial. [F. Castro's defence speech at his trial in Santiago de Cuba, october, 1953. R. Debray's declaration to the military court at Camiri, Bolivia, november, 1967] (Lorrimer Publishing, 1968)
Third World series, ed. by M. Alexandre.